Changes in Qualitative and Quantitative Ultrasound Assessment of the Gastric Antrum Before and After Elective Caesarean Section in Term Pregnant Women: A Prospective Cohort Study. Issue 3 (September 2017) - Rouget, C.; Chassard, D.; Bonnard, C.; Pop, M.; Desgranges, F.P.; Bouvet, L.
Abstract : ( Anaesthesia. 2016;71(11):1284–1290) Ultrasound examination of the gastric antrum is used for qualitative analysis of gastric contents and to estimate gastric fluid volume before general anaesthesia in nonpregnant adults and children. There are published values correlating antral cross-sectional area (CSA) with a quantitative measure of gastric contents. In parturients, however, the relationship between the antral area and gastric contents might be altered as the gravid uterus changes the position and size of the stomach through direct compression. Therefore, a prospective study was carried out to determine the antral CSA and the quantitative estimate of gastric contents before and after cesarean section (CS).